Surface finishing of intricate metal mould structures by large-area electron beam irradiation - Murray, J.W.; Kinnell, P.K.; Cannon, A.H; Bailey, B.; Clare, A.T. (Elsevier, 2013)
The advancement of polymer moulding tools is increasingly focused on imparting not only form but also surface texture for functionality to the surfaces of parts that are created. Furthermore, the increasing demand for inexpensive and higher quality micro-components means that tools for replication processes must take advantage of advanced manufacturing techniques. Tools created by processes such as micro-investment casting, as in this case, may often suffer from excessive surface roughness, malformed edges and general deformation. This results in higher de-moulding forces and a reduction in fidelity of moulded parts to design intent. In this study, large-area electron beam irradiation (EB) is shown to be an effective technique for improving these metrics. For the first time, large population, high aspect ratio micro-features are subject to this process and the mechanisms of smoothing and key enhancement phenomena are demonstrated. The possibility of including EB irradiation in an integrated process chain for arriving at net shape is also discussed.